Michael Psellos on literature and art : a Byzantine perspective on aesthetics - Psellus, Michael; Papaioannou, Stratis (Michael Psellos in translation., 2017)
The ambition of Michael Psellos on Literature and Art is to illustrate an important chapter in the history of Greek literary and art criticism and introduce precisely this aspect of Psellian writing to a wider public.